2017
DOI: 10.1016/j.neuropsychologia.2017.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Lexical access in semantic variant PPA: Evidence for a post-semantic contribution to naming deficits

Abstract: The most salient clinical symptom of semantic variant primary progressive aphasia (PPA) is a profound and pervasive anomia. These patients' naming impairments have been shown to reflect in large part a domain-general deterioration of conceptual knowledge that impacts both linguistic and non-linguistic processing. However, it is possible that post-semantic stages of lexical access may also contribute to naming deficits. To clarify the stages at which lexical access breaks down in semantic variant PPA, eleven Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…However, it has been shown that even early stage lv-PPA patients have subtle semantic disorders when tested with psycholinguistic paradigms ( 64 ), which is coherent with our imaging findings revealing the involvement of anterior portions of the temporal lobe contributing to semantics. Likewise, sv-PPA patients have, in addition to semantic breakdown, lexical disorders as revealed by psycholinguistic testing ( 64 , 65 ), which is coherent with our imaging findings revealing the involvement of posterior portions of the temporal lobe implementing the mental lexicon.…”
Section: Discussionsupporting
confidence: 90%
“…However, it has been shown that even early stage lv-PPA patients have subtle semantic disorders when tested with psycholinguistic paradigms ( 64 ), which is coherent with our imaging findings revealing the involvement of anterior portions of the temporal lobe contributing to semantics. Likewise, sv-PPA patients have, in addition to semantic breakdown, lexical disorders as revealed by psycholinguistic testing ( 64 , 65 ), which is coherent with our imaging findings revealing the involvement of posterior portions of the temporal lobe implementing the mental lexicon.…”
Section: Discussionsupporting
confidence: 90%
“…In this case, semantic representations themselves are intact but cannot be accessed reliably. This may occur in the early stages of svPPA, in which comprehension is still relatively intact but individuals appear to have reduced naming abilities because of weakened access to semantic representations in language production (Mesulam et al, 2009; Wilson, Dehollain, Ferrieux, Christensen, & Teichmann, 2017).…”
Section: Storage Deficits and Response Consistency In Svppamentioning
confidence: 99%
“…In this case, semantic representations themselves are intact but cannot be accessed reliably. This may occur in the early stages of svPPA, in which comprehension is still relatively intact but individuals appear to have reduced naming abilities because of weakened access to semantic representations in language production (Mesulam et al, 2009;Wilson, Dehollain, Ferrieux, Christensen, & Teichmann, 2017). Warrington and Shallice (1979) proposed that one of the main characteristics that can be used to distinguish between a storage deficit and an access deficit is response consistency.…”
Section: Storage Deficits and Response Consistency In Svppamentioning
confidence: 99%
“…In this case, semantic representations themselves are intact but cannot be accessed reliably. This may occur in the early stages of svPPA, where comprehension is still relatively intact but individuals appear to have reduced naming abilities due to weakened access to semantic representations in language production (Mesulam et al, 2009;Wilson, Dehollain, Ferrieux, Christensen, & Teichmann, 2017). Warrington and Shallice (1979) proposed that one of the main characteristics that can be used to distinguish between a storage deficit and an access deficit is response consistency.…”
Section: Storage Deficits and Response Consistency In Svppamentioning
confidence: 99%